Heat Transfer Enhancement Using Nanofluids in an Automotive Cooling System - K., Kadirgama; Hussein, Adnan M.; R. A., Bakar; Sharma, Korada Viswanatha (Elsevier, 2014)
The increasing demand of nanofluids in industrial applications has led to increased attention from many researchers. In this paper, heat transfer enhancement using TiO2 and SiO2 nanopowders suspended in purewater is presented. The test setup includes a car radiator, and the effects on heat transfer enhancement under the operating conditions are analyzed under laminar flow conditions. The volume flow rate, inlet temperature and nanofluid volume concentration are in the range of 2–8 LPM, 60–80 °C and 1–2% respectively. The results showed that the Nusselt number increased with volume flow rate and slightly increased with inlet temperature and nanofluid volume concentration. The regression equation for input (volume flow rate, inlet temperature and nanofluid volume concentration) and response (Nusselt number) was found. The results of the analysis indicated that significant input parameters to enhance heat transfer with car radiator. These experimental results were found to be in good agreement with other researchers' data, with a deviation of only approximately 4%.